ANALISIS NILAI PERUSAHAAN DI PENGARUHI TERHADAP PROFITABILITAS, UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL - Gautama, Jennifer Fernanda; Ekadjaja, Agustin (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research objectives to obtain empirical evidence on the effect of profitability, company size and institutional ownership on company value. The company value is using the dependent variable and the independent variables used are profitability, company size and institutional ownership. The population in this research are consumer cyclicals (main) companies listed on the Indonesia Stock Exchange in 2016-2020 period. The samples collected using the Purposive Sampling method of 40 companies, which research samples of 27 companies with a total data of 135 samples used. The results of the data used secondary data sourced from the financial statements of companies listed on the Indonesian Stock Exchange. The data analysis technique used in this research is multiple linear regression analysis, t test and F test. This study shows that 1) profitability has a positive and significant effect on firm value. 2) firm size has a positive and insignificant effect on firm value. 3) institusional ownership has a positive and in significant effect on firm value.